When "separate" may be better: Exploring single-sex learning as a remedy for social anxieties in female middle school students. Issue 2 (14th March 2016) - Hart, Laura C.
Abstract: Research on the overall effectiveness of single-sex education remains inconclusive; however, some research does indicate that benefits other than academic achievement may be possible with a single-sex format. Advocates argue that when single-sex environments are structured by not only separating boys and girls but also by leveraging gender-specific learning strategies, positive outcomes are more likely. This may be of particular significance for middle-school girls, who often struggle with social anxieties related to adolescence that create barriers in transitioning to and navigating the middle school environment. As issues for middle-school girls are often unique to their gender, single-sex education emerges as a possible remedy to these problems. This study used qualitative data collected over a three-year period at a single-school site. Participant responses consistently showed that 6th grade girls placed in a single-sex classroom found the setting to be more supportive than a traditional mixed-sex classroom. Emerging themes included perceived improvement of academic performance and increased focus and engagement. Overall results indicated that for middle school females, participation in single-sex programs can help in easing social anxieties girls may experience while in middle school.